2014
DOI: 10.1097/nmd.0000000000000124
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Its Factors Affect Cognitive Function in Chronic Schizophrenia Complicated by Metabolic Syndrome

Abstract: The aim of this study was to investigate the characteristics of cognitive function damage in chronic schizophrenia patients with metabolic syndrome (MS); 388 patients were divided into two groups: MS group (180 people with schizophrenia and MS) and non-MS group (208 people with schizophrenia but without MS). The Positive and Negative Syndrome Scale (PANSS) and the Treatment Emergent Symptom Scale (TESS) were used to evaluate clinical symptoms and drug adverse reaction. The Repeatable Battery for the Assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 27 publications
1
20
0
1
Order By: Relevance
“…That worse premorbid cognitive functioning in early adolescence and not social functioning is associated with the co‐occurrence of MS in schizophrenia has not been reported previously. Like others , we found a relationship between MS and current cognitive functioning. Participants with comorbid MS performed worse in terms of IQ, immediate and delayed memory, speed of processing and vigilance as compared to those without MS. Only one study failed to detect a relationship between MS and cognition , which can be explained by discrepancies in demographics and the use of different MS criteria.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…That worse premorbid cognitive functioning in early adolescence and not social functioning is associated with the co‐occurrence of MS in schizophrenia has not been reported previously. Like others , we found a relationship between MS and current cognitive functioning. Participants with comorbid MS performed worse in terms of IQ, immediate and delayed memory, speed of processing and vigilance as compared to those without MS. Only one study failed to detect a relationship between MS and cognition , which can be explained by discrepancies in demographics and the use of different MS criteria.…”
Section: Discussionsupporting
confidence: 89%
“…Lindenmayer et al reported associations between MS diagnosis and cognitive impairment (i.e., worse processing speed, working memory, and problem‐solving). Boyer et al confirmed this and reported that worse memory, attention, and flexibility were associated with MS. Li et al also found an association between MS and impaired cognition in terms of lower attention, immediate and delayed memory scores. However, Meyer et al failed to show an association between MS and neurocognitive composite score, consisting of (working) memory, processing speed, vigilance, and reasoning.…”
Section: Introductionmentioning
confidence: 93%
“…Recently it has been described that MetS might aggravate injury of cognitive function in chronic schizophrenia, especially in immediate memory, delayed memory, and attention (Li et al, 2014).…”
Section: Metabolic Syndromementioning
confidence: 99%
“…Further, patients with schizophrenia experience significant disability accounting for 1.1% of total disability‐adjusted‐life‐years and 2.8% of years‐lost‐to‐disease, due primarily to cognitive impairment . Metabolic syndrome has been shown to independently affect cognitive function . Thus, patients with schizophrenia have double jeopardy, as a result of the illness (e.g.…”
mentioning
confidence: 99%
“…5 Metabolic syndrome has been shown to independently affect cognitive function. 6 Thus, patients with schizophrenia have double jeopardy, as a result of the illness (e.g. cognitive impairment) and also secondary to the adverse metabolic health consequences associated with medications.…”
mentioning
confidence: 99%